Manajemen Pengelolaan Pendidikan Islam Anak Usia Dini (PIAUD) Berbasis Al-Quran - Supriadi - Supriadi; Yesy Arikarani; Pasiska Pasiska; Joni Helandri (STAI Bumi Silampari, 2023)
This journal discusses the management of Al-Quran-based early childhood Islamic education (PIAUD). Early childhood Islamic education is a critical stage in child development, which requires good management to ensure the formation of Islamic character. In this context, the Koran has great potential as a source of guidance in the management of PIAUD. The purpose of this research is to identify and explain an effective management approach in the management of Al-Quran-based PIAUD. The theoretical basis includes the concept of PIAUD, the concept of management, and the significance and approach of the Koran in the context of PIAUD. The research method used is literature analysis and case studies. The results showed that the Al-Quran-based PIAUD management included educational program planning, institutional organization, learning implementation, as well as evaluation and development. The case studies describe the implementation of Al-Quran based management in PIAUD and its positive impact on children and the environment. In conclusion, Al-Quran-based PIAUD management has great potential to shape Islamic character in early childhood. The implications of this research can be used as a reference in developing PIAUD programs that are more effective and relevant to the values of the Al-Quran.